Antecedents to Websıte E-Commerce Satısfactıon and Loyalty - Effed Darta; Muhammad Yasser Iqbal Daulay; Willy Abdillah (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
This study explores the major determinants of feedback on shopping satisfaction. This research is essential to provide empirical evidence about the factors that can ensure customer satisfaction and loyalty. By surveying respondents that are users of e-commerce website services, this study uses the construct validity test using the Partial Least Square (PLS) method with SmartPLS software application version 2.0. The results explain the visual involvement variable does not correlate with customer satisfaction and loyalty. The interactivity website variable has a strong relationship with customer satisfaction and loyalty. Therefore, customers need service communication interactivity for service providers and merchants. This research contributes to the development of consumer experience theory and online consumer experience.